How can we make the psychiatric workforce more family focused? - Mayber Darryl (2018)
© Cambridge University Press (1996, 2004) 2015. Multiple international studies indicate that very few family members including children receive interventions or support when their relative with mental illness is receiving treatment (e.g., Rummel-Kluge et al., 2006). This chapter focuses upon workforce issues, particularly how the psychiatric workforce can be supported to be family focused. Initially, the chapter outlines what we mean by family approaches and then overviews our conception of a continuum of family-focused care and expectations for psychiatric agencies and workers. A brief theoretical review of family-focused care is then outlined followed by information about barriers and enablers to family-focused practice. The chapter ends with reflections from multiple countries regarding the current state of family-focused practice and potential ways forward in each country. As outlined throughout this book, mental illness can be disabling, but when such patients are parents their children can also be adversely affected. Having such parents significantly increases the likelihood of children developing a mental disorder themselves compared to other children in the community (Hosman et al., 2009) along with a multitude of associated risks (e.g., emotional, school, and relationship problems) (Reupert and Maybery, 2007). At the same time, research has clearly demonstrated the benefits of family-focused practice to parents, as well as their children and other family members (Siegenthaler et al., 2012). However, throughout the world, the psychiatric workforce rarely seems to respond to children and families where a parent has a mental illness. Children living in such families have been described as “hidden” because workers are often unaware that service users are parents with dependent children (Fudge and Mason, 2004). A study of German, Austrian, and Swiss psychiatric institutions found that only 2% of family members received any form of psychoeducation (Rummel-Kluge et al., 2006). That means 98% of family members received no information about mental illness from these psychiatric institutions.